A new low-cost method of virtual cardiac dissection of computed tomographic datasets - Saurabh Kumar Gupta; Diane E Spicer; Robert H Anderson (Wolters Kluwer Medknow Publications, 2019)
Computed tomography has an established role in the evaluation of a variety of cardiac disorders, including congenital heart diseases. The current generation of high-speed scanners produces volumetric data at low doses of radiation. The interpretation of cardiac anatomy, however, is generally limited to multiplanar assessment of two-dimensional images. The volume rendering technique provides an excellent three-dimensional demonstration of external morphology but offers little information about the intracardiac anatomy. The alternative approach of virtual cardiac dissection, which is a modification of volume rendering, on the other hand, provides crucial insights regarding the intracardiac anatomy. At present, virtual cardiac dissection requires expensive software packages. These software packages are not available in all countries, thus limiting its use in routine clinical care. We present here the details of a newly developed technique that permits virtual cardiac dissection using a personal computer and open-source software. Our technique involves no additional cost and can be achieved in the comfort of the office or operating room of the cardiologist, radiologist, or cardiac surgeon. This enhanced three-dimensional visualization of intracardiac anatomy will surely improve the understanding of the morphological details of both normal and malformed hearts. In addition, by permitting assessment in projections with which modern-day cardiologists and cardiac surgeons are conversant, it is likely to improve clinical decision-making. We illustrate here its potential utility in the morphologic assessment of the atrial septum and its deficiencies, along with malformations of the ventricular outflow tracts, including common arterial trunk.